2020
DOI: 10.1016/j.foodchem.2020.127528
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of chlorogenic acid inhibits lipid oxidation: An investigation using multi-spectroscopic methods and molecular docking

Abstract: Endogenous lipase and lipoxygenase play important roles in accelerating lipid oxidation.Polyphenols are a series of commonly used chemicals for preserving fish and seafood products, due to their positive inhibitory effects on lipid oxidation. However, the mechanism involved is still unknown. The inhibitory effects of chlorogenic acid (CGA) on lipase and lipoxygenase were investigated and explored with multi-spectroscopic and molecular docking approaches. Results showed that CGA could inhibit the activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 39 publications
4
28
0
Order By: Relevance
“…Δ G° < 0 manifested that this binding was spontaneous 44 . Values of Δ H° and Δ S° were −97.57 kJ/mol and −241.23 J/mol K, indicating that the binding between chlorogenic acid and lipase was also mainly attributed to hydrogen bond and van der Waals forces 23 …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Δ G° < 0 manifested that this binding was spontaneous 44 . Values of Δ H° and Δ S° were −97.57 kJ/mol and −241.23 J/mol K, indicating that the binding between chlorogenic acid and lipase was also mainly attributed to hydrogen bond and van der Waals forces 23 …”
Section: Resultsmentioning
confidence: 96%
“…It determined that the quenching mechanism was static quenching 33 . The quenching mechanism Ligupurpuroside B, chlorogenic acid binding with lipase were also static quenching 23,38 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there were hydrophobic interactions between 15 residues of the protease, such as Val‐229, Ala‐234, His‐230, Ile‐242, Asn‐376, Asn‐376, Thr‐362, Glu‐209, Asp‐363, Glu‐180, Val‐ 277, Pro‐124, Met‐384, Thr‐119, Phe‐123, Phe‐388 and Gln‐243, and nine residues of myosin light chain, such as His‐119, Phe‐110, Lys‐12, Ser‐3, Met‐1, Gln‐16, Pro‐15, Leu‐126 and Gly‐131. Thus, hydrogen bonds and hydrophobic interactions are the major interactive forces that promote the binding of protease and myosin light chain and also can accelerate the catalysis effect of protease on substrate 49 . In addition, related studies have shown that protease may cleave the substrate protein correctly through the hydrogen bond between the protease and substrate 50 .…”
Section: Resultsmentioning
confidence: 99%
“…The bound conformations and binding sites of ligand and protein were further analyzed based on the calculation results (Cao et al, 2020).…”
Section: Molecular Dockingmentioning
confidence: 99%